2020
DOI: 10.5603/fhc.a2019.0022
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3a aggravates inflammation and induces apoptosis in IL-1-treated rabbit chondrocytes via positively regulating tenascin-c

Abstract: Introduction. Osteoarthritis (OA) is the most common degenerative disease in middle-aged and elderly individuals that causes joint deformity and limb disability. Accumulating evidence has suggested that the pathogenesis of OA has been related to various mechanisms such as apoptosis, inflammation, oxidative stress and metabolic disorders. The aim of this study is to clarify the role of Foxo3a in the progress of OA in an in vitro model. Materials and methods. The chondrocytes were derived from rabbit, and treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Furthermore, IL-1β causes synoviocytes and chondrocytes to secrete degenerative enzymes such as MMPs. The cytokine receptors on articular chondrocyte surfaces are activated by IL-1β, which leads to the activation of the NF-κB signaling pathway [ 31 , 32 ]. This signaling pathway inhibits chondrocyte anabolic activity, either alone or in conjunction with other signaling pathways [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, IL-1β causes synoviocytes and chondrocytes to secrete degenerative enzymes such as MMPs. The cytokine receptors on articular chondrocyte surfaces are activated by IL-1β, which leads to the activation of the NF-κB signaling pathway [ 31 , 32 ]. This signaling pathway inhibits chondrocyte anabolic activity, either alone or in conjunction with other signaling pathways [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In OA joints, IL-1β can trigger apoptosis of chondrocytes [ 34 ]. Furthermore, when human chondrocytes from normal and OA cartilage were treated with human IL-1β, apoptosis increased [ 31 ]. Similarly, through DCF fluorescence, we showed that IL-1β incubation increased ROS production.…”
Section: Discussionmentioning
confidence: 99%